Breastfeeding women in need of information about antiemetics for nausea and vomiting during pregnancy: a review of inquiries to a medicines information service - Heitmann, Kristine; Bakkebø, Tina; Havnen, Gro C.; Schjøtt, Jan (Frontiers in Pharmacology, 2023)
Introduction: The medicines information service, SafeMotherMedicine, regularly receives inquiries from breastfeeding women asking about antiemetics for nausea and vomiting during pregnancy (NVP) or hyperemesis gravidarum (HG). However, treatment guidelines for NVP or HG do not address the use of antiemetics in women who are breastfeeding while becoming pregnant again. Our objective was to characterize inquiries to describe the need for lactation risk information among women with NVP or HG and also to raise awareness of this topic. Method: We conducted a review of inquiries to the Norwegian web-based medicines information service, SafeMotherMedicine. Results: In total, 97 inquiries addressing the use of antiemetics for NVP or HG during breastfeeding were identified. The following medications were addressed in the inquiries (n = 97): meclizine (51%), metoclopramide (33%), promethazine (16%), ondansetron (9%), and others (6%). The breastfed child was older than 6 months and 1 year in 96% and 71% of the inquiries, respectively. There was a preponderance of general inquiries (unclear motivation/double checking) (64%); however, one-third of the inquiries were generated by restrictive information from sources such as product information. Conclusion: Based on our small review of spontaneous inquiries, there seems to be an information need about the use of antiemetics during lactation among women breastfeeding an older infant whilst suffering from NVP or HG. Addressing such use in guidelines for NVP and HG and/or other easily available information sources may be considered in order to balance out the restrictive information provided by the manufacturers. This could avoid potential unnecessary weaning of breastfeeding in an otherwise challenging situation.